Identification of a cryptic bacterial promoter in mouse (mdr1a) P-glycoprotein cDNA - Pluchino, KM; Esposito, D; Moen, JK; Hall, MD; Madigan, JP; Shukla, S; Procter, LV; Wall, VE; Schneider, TD; Pringle, I; Ambudkar, SV; Gill, D; et al. (Public Library of Science, 2015)
The efflux transporter P-glycoprotein (P-gp) is an important mediator of various pharmacokinetic parameters, being expressed at numerous physiological barriers and also in multidrug-resistant cancer cells. Molecular cloning of homologous cDNAs is an important tool for the characterization of functional differences in P-gp between species. However, plasmids containing mouse mdr1a cDNA display significant genetic instability during cloning in bacteria, indicating that mdr1a cDNA may be somehow toxic to bacteria, allowing only clones containing mutations that abrogate this toxicity to survive transformation. We demonstrate here the presence of a cryptic promoter in mouse mdr1a cDNA that causes mouse P-gp expression in bacteria. This expression may account for the observed toxicity of mdr1a DNA to bacteria. Sigma 70 binding site analysis and GFP reporter plasmids were used to identify sequences in the first 321 bps of mdr1a cDNA capable of initiating bacterial protein expression. An mdr1a M107L cDNA containing a single residue mutation at the proposed translational start site was shown to allow sub-cloning of mdr1a in E. coli while retaining transport properties similar to wild-type P-gp. This mutant mdr1a cDNA may prove useful for efficient cloning of mdr1a in E. coli.